O estereótipo viking no cinema: as representações do mito do Ragnarök nos filmes da contemporaneidade - Silva, Mirelly Maciel da (2019)
The Ragnarök myth, found in the mitografica Edda Poética arouses curiosity about Nordic eschatology. Thus, we sought to analyze the representations and manifestations of the myth of this assumption. We propose to understand how the idea of the end of the world spread within social, cultural, artistic and religious representations. As we entered the mythological space, we sought to understand how the Ragnarök myth was appropriated by today's society. As we look into this view, we will see how the Norse myth reconfigured and became common in contemporary society. This mitografica narrative of the Vikings was driven by the popularization of the media in the last century XXI. The popularization of the myth characterized the Vikings peoples in an allegorical and homogeneous manner. Given this homogenization of the media about the Vikings, we will investigate how their stereotypes were built and how they are represented in cinema. This research starts from an in-depth study between the sciences of religions, the representations and manifestations of myth and its socioculturais and historical characterization. Erik the Viking (1989), Gåten Ragnarök (2013), Thor: Ragnarok (2017) presented themselves as interesting sources to know the myth and its representations